TEI Lex-0 Etym: Toward Terse Recommendations for the Encoding of Etymological Information - Jack Bowers; Axel Herold; Toma Tasovac; Laurent Romary (Journal of the Text Encoding Initiative)
The present paper describes the specific contribution of the TEI Lex-0 initiative, which aims to define a terser subset of the TEI Guidelines for the representation of etymological features in dictionary entries. Going beyond the basic provision of etymological mechanisms in the TEI Guidelines, TEI Lex-0 Etym proposes a systematic representation of etymological and cognate descriptions by means of embedded constructs based on the (for etymologies) and (for etymons and cognates) elements. In particular, given that all the potential contents of etymons are highly analogous to those of dictionary entries in general, the contents presented herein heavily reuse many of the corresponding features and constraints introduced in other components of TEI Lex-0 for the encoding of etymologies and etymons. The TEI Lex-0 Etym model is also closely aligned with ISO 24613–3 on modeling etymological data and the corresponding TEI serialization available in ISO 24613–4.